2021
DOI: 10.3390/ijms22158045
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Placental CD24 in Preterm Preeclampsia Is an Indicator for a Failure of Immune Tolerance

Abstract: Introduction: CD24 is a mucin-like glycoprotein expressed at the surface of hematopoietic and tumor cells and was recently shown to be expressed in the first trimester placenta. As it was postulated as an immune suppressor, CD24 may contribute to maternal immune tolerance to the growing fetus. Preeclampsia (PE), a major pregnancy complication, is linked to reduced immune tolerance. Here, we explored the expression of CD24 in PE placenta in preterm and term cases. Methods: Placentas were derived from first and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…As was previously reported [27,28], it was also found that the protein is co-expressed with Siglec-10, mainly in the close vicinity of the invasive extravillous trophoblasts [34]. In another study, we used qRT-PCR analysis to show a significant increase in CD24 expression from the first and early second trimester to the third trimester and term delivery [35]. In contrast to the normal course of pregnancy, in cases of early (before 34 weeks gestation), and preterm (before 37 weeks gestation) preeclampsia, the level of CD24 mRNA is reduced [35] compared to cases of term delivery and preterm delivery (before 37 weeks gestation).…”
Section: Introductionsupporting
confidence: 67%
“…As was previously reported [27,28], it was also found that the protein is co-expressed with Siglec-10, mainly in the close vicinity of the invasive extravillous trophoblasts [34]. In another study, we used qRT-PCR analysis to show a significant increase in CD24 expression from the first and early second trimester to the third trimester and term delivery [35]. In contrast to the normal course of pregnancy, in cases of early (before 34 weeks gestation), and preterm (before 37 weeks gestation) preeclampsia, the level of CD24 mRNA is reduced [35] compared to cases of term delivery and preterm delivery (before 37 weeks gestation).…”
Section: Introductionsupporting
confidence: 67%
“…S6o, Supplementary Table 7). Interestingly, reduced global placental CD24 expression has been associated with an increased risk of developing preterm preeclampsia, yet EVT-specific expression of CD24 transcripts has not yet been reported 65, 72 . Given that abnormal decidual and spiral artery remodeling are thought to play a major role in preeclampsia 73 , we sought to determine if other genes involved in EVT invasion and vascular remodeling had previously been implicated as well.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the knowledge attitude and practices are not beneficial for increasing their concern about this dangerous disease. Apart from that, the attitude also shows that they need a proper awareness program in this context for proceeding with the best result (Sammar et al 2021). Not only that, it can be seen that preeclampsia affected arteries that carry blood flow to the placenta.…”
Section: Results Data Interpretation By Spss Frequency Distributionmentioning
confidence: 99%